Educational Methods Deduced from Surat Yunus - Awda, Raad; Hamdi , Ziad (Islamic Sciences Journal, 2023)
ABSTRACT This study aimed to elicit educational methods in Surat Yunus, so the deductive approach was followed, by reference to the approved books of interpretation, Sahih al-Sunan, books of explanations of hadith and Sunnah, language dictionaries, history books of historians to whom the nation attests to justice and trust, and other approved books adopted by the researchers, and the researchers did not rely on weak hadiths and traces during the studying of this research.